The effect of the flipped classroom strategy on motivation to learn mathematics among 9th-grade female students: a quasi-experimental study in Amman - Mansour, Othman; Wardat, Yousef (Frontiers in Education, 2025)
IntroductionThe flipped classroom strategy (FCS) reimagines traditional instruction by shifting lectures and content delivery outside the classroom, enabling face-to-face time for active, collaborative learning. This study investigates the impact of FCS on the motivation to learn mathematics among 9th-grade female students in Wadi Al-Seer, Amman, Jordan, addressing a gap in understanding its effectiveness in this specific demographic.MethodsAdopting a quasi-experimental design, 61 students from a single public school were randomly assigned to an experimental group (n = 31, receiving FCS) or a control group (n = 30, following a conventional model). A 31-item Mathematics Learning Motivation Scale (MLMS) was administered to both groups before and after a 12-week intervention to assess changes in motivation. Data were analyzed to compare motivation scores between the groups.ResultsThe analysis revealed a statistically significant increase in motivation scores for the experimental group (adjusted mean = 4.27) compared to the control group (adjusted mean = 3.11), with an effect size of 81.9% (p = 0.000). These findings demonstrate that FCS substantially enhances students’ engagement and motivation in mathematics.DiscussionThe results suggest that FCS is an effective approach for boosting motivation in mathematics learning among the studied population. The study recommends integrating FCS methodologies into teacher training programs and calls for future research to explore its effectiveness across diverse educational contexts to validate and extend these findings.